Tantalisingly Close An Archaeology of Communication Desires in Discourses of Mobile Wireless Media - de Vries, Imar (Amsterdam University Press, 2012)
While studies of mobile wireless communication devices usually focus on their social implications, De Vries proposes to venture into a more historical and comparative direction to shed light on our preoccupation with them in the first place. He constructs an archaeological view of the development of communication technologies over the past 200 years, providing a comprehensive account of how persistent hopes and beliefs have come to give mobile wireless media such a prominent position today. Our expectations and uses of them are surprisingly similar to those of older media; consequently, they reconfirm the idea that living in an 'anyone, anything, anytime, anywhere' world is both a blessing and a curse, and that the desire for sublime communication is a tragic yet highly powerful regulative principle in our media evolution.